Evaluation Of Development Of Medical Check-Up Services At Putri Hijau Hospital - Lexandria Grandis G. D.; Ermi Girsang; Maya Sari Mutia; Ali Napiah Nasution (CV. Inara, 2022)
The medical check-up service process has several challenges such as the quality of medical personnel, the complexity of the work, long waiting times, uncomfortable patient waiting areas, the quality of medical equipment, and decreased visits. Seeing the medical check-up business opportunity, hospitals must continue to evaluate the MCU service business process so that the use of resources for these services becomes more efficient. The purpose of this study is to evaluate the development of medical check-up services. This study uses a quantitative analytical survey technique with a cross-sectional approach. The research was conducted at Putri Hijau Hospital Level II Medan. The population and research sample are 7 key persons. Sampling by purposive sampling. Data analysis was carried out using the Internal Factor Analysis Strategic (IFAS) matrix, External Factor Analysis Strategic (EFAS) matrix, and SWOT analysis. The results showed that internal factors that have the potential as strengths in the development of medical check-up services at the Putri Hijau Hospital Level II Medan are the quality of administrative staff, quality of functional staff, number of collaborating companies, ease of payment, ability to build good relations, waiting room for medical services. check-up, medical and non-medical equipment in the medical check-up room. Internal factors of weakness are marketing installation, marketing organization, marketing funds, marketing managerial ability, and condition of the size of the examination room. Opportunity external factors are the labor law, the acceptance of military recruits, and the many companies that cooperate. External threats are the quality of medical check-ups at competing hospitals and the Covid-19 pandemic.